Kontribusi Pendapatan Keluarga Diluar Usaha Perikanan Terhadap Pendapatan Total Rumah Tangga Nelayan Kecamatan Teluk Meranti Kabupaten Pelalawan Provinsi Riau - Fira Noprita; Muhammad Ramli; Zulkarnaini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research has been conducted at Teluk Meranti District Pelalawan Riau Province at 25 August – 25 September 2014. The method used was survey method and 20 fisherman was determined as sample with simple random sampling. The purpose of this research was to know job types and job contribution apart of fisheries business to fisherman’s household total income.Teluk Meranti have fisheries potential especially in catch fishing and also odd job for fisherman. Fisherman do odd job such as a merchant, construction worker, shopkeeper, mobile service, laborer, ABK, temporary employee and farmer. Contribution percentage of each work type was about 3,76% - 39,76%, which 5,85% - 15,68% for laborer contribution, 16,76% - 21,19% for construction worker contribution, 9,53% - 16,11% for merchant contribution, 18,01% for mobile service contribution, 14,35% - 15,55% for shopkeeper contribution, 23,43% - 25,63% for ABK contributionand 21,01% for temporary employee contribution to household economic income.Keywords : Contributions , Revenue outside fisheries , total revenue